Nicotine Facilitates Facial Stimulation-Evoked Mossy Fiber-Granule Cell Long-Term Potentiation in vivo in Mice - Cao, Li-Xin; Bing, Yan-Hua; Xu, Yin-Hua; Zhang, Guang-Jian; Chu, Chun-Ping; Hong, Lan; Qiu, De-Lai (Frontiers in Cellular Neuroscience, 2022)
Nicotine is a psychoactive component of tobacco that plays critical roles in the regulation of neuronal circuit function and neuroplasticity, and contributes to the improvement of working memory performance and motor learning function via nicotinic acetylcholine receptors (nAChRs). Under in vivo conditions, nicotine enhances facial stimulation-evoked mossy fiber-granule cell (MF-GrC) synaptic transmission, which suggests that nicotine regulates MF-GrC synaptic plasticity in the mouse cerebellar cortex. Here, we investigated the effects of nicotine on facial stimulation-induced long-term potentiation (LTP) of MF-GrC synaptic transmission in urethane-anesthetized mice. Our results showed that facial stimulation at 20 Hz induced a MF-GrC LTP in the mouse cerebellar granular layer that was significantly enhanced by the application of nicotine (1 μM). Blockade of α4β2 nAChRs, but not α7 nAChRs, during delivery of 20 Hz facial stimulation prevented the nicotine-induced facilitation of MF-GrC LTP. Notably, the facial stimulation-induced MF-GrC LTP was abolished by N-methyl-D-aspartate (NMDA) receptor antagonist, but it was restored by additional application of nicotine during delivery of 20 Hz facial stimulation. Furthermore, antagonism of α4β2 nAChRs, but not α7 nAChRs, during delivery of 20 Hz facial stimulation prevented nicotine-induced MF-GrC LTP. Moreover, inhibition of nitric oxide synthase (NOS) abolished the facial stimulation-induced MF-GrC LTP, as well the effect of nicotine on it. Our results indicated that 20 Hz facial stimulation induced MF-GrC LTP via an NMDA receptor/nitric oxide (NO) cascade, but MF-GrC LTP was enhanced by nicotine through the α4β2 AChR/NO signalling pathway. These results suggest that nicotine-induced facilitation of MF-GrC LTP may play a critical role in the improvement of working memory performance and motor learning function.